Management of Electrical Modernization in Construction with the Comparison between Standard and Flexible Approach in the Economic Aspects. (2015) - Nowotarski, Piotr; Milwicz, Roman
Abstract: Modern LED lightning technology has many advantages and many building administrators and owners are considering modernization of lightning system. Modernization can be done in many ways, also using flexible and agile methods. Article describes new approach of flexible management of electrical modernization with comparison to standard approach in economic aspects on the example of building complex modernization in Poland. Main differences and advantages of both solutions are discussed with focus on the waste management problem and initial investments costs, which are crucial from the point of view of investors considering similar modernizations.